A thin empty-shell bismuth tungstate hierarchical structure constructed by the acid sculpture effect with improved visible-light photocatalytic activity1. (2nd June 2015) - Li, Chunmei; Chen, Gang; Sun, Jingxue; Feng, Yujie; Dong, Hongjun; Han, Zhonghui; Hu, Yidong; Lv, Chade
<x xml:space="preserve">Abstract</x> A thin empty-shell Bi2WO6 hierarchical structure is constructed using a simple acid sculpture strategy, which shows excellent photocatalytic activity.